The Efficacy of Soursop Leaf Extract as a Hepatoprotector in White Rats Rattus norvegicus Induced by the Antituberculosis Drugs Isoniazid and Pyrazinamide - Runggu Retno Justiani Napitupulu; Jenny Ria Sihombing; Bernika Ayu Frastika; Greace Ari Sulastry Aritonang (Sean Institute, 2023)
The use of antituberculosis drugs isoniazid and pyrazinamide triggers hepatotoxicity. Soursop leaves have a hepatoprotective effect because they contain antioxidant compounds that can help inhibit and prevent oxidative damage to the liver. This study aims to determine the effect of soursop leaf extract on the histopathological appearance of rat liver induced by isoniazid and pyrazinamide. This research is a laboratory experimental research using design posttest only control group design. This study used 24 rats Wistar divided into four groups and given treatment for 14 days. The negative control group was not given soursop leaf extract. The positive control group was given isoniazid and pyrazinamide, the treatment group I was given isoniazid and pyrazinamide and 1 hour later continued with soursop leaf extract 72 mg/day giving soursop leaf extract 144 mg/day. The dose of isoniazid used was 189 mg/day, while the dose of pyrazinamide was 252 mg/day. Termination of rats was carried out on the 15th day to collect rat liver organs. Furthermore, histopathological examination of the rat liver was carried out. The results showed that the rats in the negative control group had normal histopathological features. In the positive control group, there was a picture of hydropic degeneration. The histopathological picture of the rat liver in the treatment group 1 showed a picture of parenchymatous degeneration and in the treatment group 2, the liver cells were normal. Administration of soursop leaf extract affected the histopathological picture of rat liver induced by isoniazid and pyrazinamide.